Parents' role in teens' personal photo sharing: a moderated mediation model incorporating privacy concerns and network size - Liu, Cong; Lwin, May; Ang, Rebecca (UI Scholars Hub, 2019)
Disclosure of personal photographs on social networking sites could lead to potential harm to adolescent users. This study aims to understand parents’ role in adolescents’ visual information disclosure on Facebook as well as the mediating role of privacy concern and moderating role of Facebook network size. A total of 351 secondary school students who use Facebook participated in the study (49.6% boys; mean age M = 13.98, SD = 0.94). Results showed a significant mediating effect of privacy concern on the relationship between parental mediation and visual disclosure (b= -0.07, Boot SE = 0.02, 95% CI [-0.116, -0.028]). Furthermore, the effect of parental mediation on privacy concern was shown to be moderated by the level of network size (b = 0.15, SE = 0.05, t = 3.04, p < 0.01). Findings contribute to a better understanding of visual disclosure drivers, particularly of the underlying mechanisms of the protective effect of parental mediation. Practical suggestions for parents are discussed.